2013
DOI: 10.12973/eurasia.2013.938a
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Disgust and Personal Experiences are Associated with Acceptance of Dissections in Schools

Abstract: Terms and conditions for use: By downloading this article from the EURASIA Journal website you agree that it can be used for the following purposes only: educational, instructional, scholarly research, personal use. You also agree that it cannot be redistributed (including emailing to a list-serve or such large groups), reproduced in any form, or published on a website for free or for a fee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
9
1
Order By: Relevance
“…Although it is possible, that approach toward hands-on and virtual dissection will change during the time according to the results of Balcombe (2000) and Fančovičová and Prokop (2014). Balcombe (2000) has reported that the approach towards hands-on dissection slowly changed and the students prefer the use of the virtual and other dissection alternative, a finding not supported by the results of our study.…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…Although it is possible, that approach toward hands-on and virtual dissection will change during the time according to the results of Balcombe (2000) and Fančovičová and Prokop (2014). Balcombe (2000) has reported that the approach towards hands-on dissection slowly changed and the students prefer the use of the virtual and other dissection alternative, a finding not supported by the results of our study.…”
Section: Discussioncontrasting
confidence: 69%
“…Several articles mentioned in the overview study (Havlíčková, & Bílek, 2015) describe significant differences in accepting of hands-on and virtual dissections between men and women, as well as students and teachers and secondary school teachers and the other teachers groups (Balcombe 2000;Fančovičová, Prokop, & Lešková, 2013;Fazal, Khan, & Yunus, 2012;Holstermann, Ainley, Grube, Roick, & Bögeholz, 2012). However, all examined differences (results not reported) between different groups were on insignificant and small levels.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations